Phenolic profile of Sercial and Tinta Negra Vitis vinifera L. grape skins by HPLC–DAD–ESI-MSn: novel phenolic compounds in Vitis vinifera L. grape - Perestrelo, Rosa Maria de Sá (2015)
This study represents the first phytochemical research of phenolic components of Sercial and Tinta Negra Vitis vinifera L. The phenolic profiles of Sercial and Tinta Negra V. vinifera L. grape skins (white and red varieties, respectively) were established using high performance liquid chromatography–diode array detection–electrospray ionisation tandem mass spectrometry (HPLC–DAD–ESI-MSn), at different ripening stages (véraison and maturity). A total of 40 phenolic compounds were identified, which included 3 hydroxybenzoic acids, 8 hydroxycinnamic acids, 4 flavanols, 5 flavanones, 8 flavonols, 4 stilbenes, and 8 anthocyanins. For the white variety, in both ripening stages, hydroxycinnamic acids and flavonols were the main phenolic classes, representing about 80% of the phenolic composition. For red variety, at véraison, hydroxycinnamic acids and flavonols were also the predominant classes (71%), but at maturity, anthocyanins represented 84% of the phenolic composition. As far as we know, 10 compounds were reported for the first time in V. vinifera L. grapes, namely protocatechuic acid-glucoside, p-hydroxybenzoyl glucoside, caftaric acid vanilloyl pentoside, p-coumaric acid-erythroside, naringenin hexose derivate, eriodictyol-glucoside, taxifolin-pentoside, quercetin-glucuronide-glucoside, malylated kaempferol-glucoside, and resveratrol dimer. These novel V. vinifera L. grape components were identified based on their MSn fragmentation profile. This data represents valuable information that may be useful to oenological management and to valorise these varieties as sources of bioactive compounds.